Iron limitation drives the globally extreme fluorescence/chlorophyll ratios of the Southern Ocean - Schallenberg, C; Strzepek, RF; Bestley, S; Wojtasiewicz, B; Trull, TW (Geophysical Research Letters, 2022)
The ratio between fluorescence (F) and chlorophyll-a (Chl)where fluorescence is measured with a saturating fluorometeris variable in the world's oceans, with the highest ratios and highest variability observed in the Southern Ocean. While species composition and Chl packaging per cell are strong drivers for the observed variability, additional factors, including iron limitation, have to this date not specifically been evaluated. Radiometers on biogeochemical (BGC)-Argo floats allow for an independent estimate of Chl concentration that is based on the light attenuation coefficient, K d . Making use of 4,000 radiometry profiles from BGC-Argo floats in the Southern Ocean, we estimate Chl based on K d and investigate the variability in F/Chl. Our analysis reveals a positive correlation between F/Chl and a proxy for iron limitation based on non-photochemical quenching dynamics. The strong influence of iron limitation on F/Chl is further corroborated by data from Southern Ocean phytoplankton cultures.